2022
DOI: 10.3389/fgene.2022.937750
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Long-Term Treatment of Autosomal Recessive Hypercholesterolemia With Lomitapide: A Subanalysis of the Pan-European Lomitapide Study

Abstract: Backgroundand aim: Autosomal recessive hypercholesterolemia (ARH) is a rare autosomal recessive disorder of low-density lipoprotein (LDL) metabolism caused by pathogenic variants in the LDLRAP1 gene. Like homozygous familial hypercholesterolemia, ARH is resistant to conventional LDL-lowering medications and causes a high risk of atherosclerotic cardiovascular diseases (ASCVDs) and aortic valve stenosis. Lomitapide is emerging as an efficacious therapy in classical HoFH, but few data are available for ARH.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…During the follow-up, the reduction in LDL-C levels was consistently maintained throughout the entire 9-year study [101]. Subanalysis showed that lomitapide is not only efficacious and safe for patients with classical HoFH but also for those with ARH [102].…”
Section: Lomitapidementioning
confidence: 84%
“…During the follow-up, the reduction in LDL-C levels was consistently maintained throughout the entire 9-year study [101]. Subanalysis showed that lomitapide is not only efficacious and safe for patients with classical HoFH but also for those with ARH [102].…”
Section: Lomitapidementioning
confidence: 84%
“…Since in case of biallelic pathogenic variants in the LDLR gene, only a very low residual activity of the LDLR is present, novel and effective therapies for HoFH are independent of the LDLR activity. These therapies include lomitapide for the inhibition of microsomal triglyceride transfer protein (MTTP), leading to a decreased production of VLDLs by the liver [ 37 , 38 ] or monoclonal antibodies for the inhibition of the Angiopoietin-Like Protein 3 (ANGPTL3), which was proved to increase IDL and LDL clearance by LDLR independent pathways [ 39 ]. Bempedoic acid is another drug acting independently of LDLR used in HeFH patients; it is an inhibitor of the ATP citrate lyase, the enzyme transforming citrate into acetyl-CoA molecules used for fatty acid synthesis [ 40 ].…”
Section: Genetics and Molecular Basismentioning
confidence: 99%